Strategy for influencing through Indonesian persuasive motivator - Ruaidah; Sumadi; Wahyudi; Nurchasanah (Universitas Muhammadiyah Malang, 2024)
The ability to persuade is a valuable communication skill that cannot be acquired easily. When used with confidence, persuasive speech possesses power, triggers change, and can inspire action. Speaking persuasively is a strategy that a motivator must master; this skill aims to influence, suggest, bring about positive change, and create attraction when speaking to an audience. This study aims to analyze the strategies used by motivators to influence participants in motivational seminars. The research employs a qualitative method with a pragmatic approach, as this approach provides strong tools for uncovering the hidden meanings in the motivator's speech. The data sources are derived from twenty (20) videos of Indonesian motivators Ary Ginanjar Agustian and Ippho Sentosa, focusing on aspects such as the topic and context of their talks. The overall findings reveal that the success of a motivator in influencing seminar participants is closely tied to three persuasive strategies used. These strategies are: i) commitment and consistency, ii) social proof, and iii) authority. The implications of this study support Robert B. Cialdini's persuasive theory, showing that the three motivators successfully persuaded, changed attitudes, and reinforced the intentions of seminar participants. Practically, the study suggests that organizations or individuals aiming to organize motivational events should select motivators with strong rhetorical skills.